Regulatory Divergence in Wound-Responsive Gene Expression between Domesticated and Wild Tomato. Issue 7 (9th May 2018) - Liu, Ming-Jung; Sugimoto, Koichi; Uygun, Sahra; Panchy, Nicholas; Campbell, Michael S.; Yandell, Mark; Howe, Gregg A.; Shiu, Shin-Han
Abstract : Profiling wound-responsive gene transcriptomes in wild Solanum pennellii and domesticated S. lycopersicum sheds light on the contribution of cis -regulatory variation to stress-responsive gene expression divergence during species domestication. Abstract: The evolution of transcriptional regulatory mechanisms is central to how stress response and tolerance differ between species. However, it remains largely unknown how divergence in cis -regulatory sites and, subsequently, transcription factor (TF) binding specificity contribute to stress-responsive expression divergence, particularly between wild and domesticated species. By profiling wound-responsive gene transcriptomes in wild Solanum pennellii and domesticated S. lycopersicum, we found extensive wound response divergence and identified 493 S. lycopersicum and 278 S. pennellii putative cis -regulatory elements (pCREs) that were predictive of wound-responsive gene expression. Only 24-52% of these wound response pCREs (depending on wound response patterns) were consistently enriched in the putative promoter regions of wound-responsive genes across species. In addition, between these two species, their differences in pCRE site sequences were significantly and positively correlated with differences in wound-responsive gene expression. Furthermore, ∼11-39% of pCREs were specific to only one of the species and likely bound by TFs from different families. These findings indicate substantial regulatory divergence in these two plant species that diverged ∼3-7 million years ago. Our study provides insights into the mechanistic basis of how the transcriptional response to wounding is regulated and, importantly, the contribution of cis -regulatory components to variation in wound-responsive gene expression between a wild and a domesticated plant species.